LOCAL WISDOM IN JAVANESE TERM: TENTREM LAN NGAJENI AS A TOLERANCE IN RURAL COMMUNITIES - Yovita Dyah Permatasari (Al Qalam, 2020)
Indonesia has a variety of religions, ethnicities, cultures, customs, and traditions. One of the attitudes that must be instilled as a good citizen is an attitude of tolerance between religious communities. This study aims to determine: what, why, and how the attitude of tolerance among religious communities is carried out in the village of Sukoreno, Jember Regency. There are 3 different religions in this area. Namely: Islam, Christianity, and Hinduism. The method used in this research is the descriptive qualitative method. It is a research method that focuses on the data obtained directly based on phenomena that exist in society. The research is carried out in-depth investigations in order to obtain the necessary information. The results of this study state that the people in the village of Sukoreno, Jember Regency are unique, which makes them able to live side by side without any conflicts that cause a break in the harmony of social life. The results of this study indicate that a key to the tolerant attitude is found, namely using the Javanese term "Tentrem Lan Ngajeni." It means peace and respect. This term was expressed by several religious experts in this area. So, that the harmony among religious communities in this Sukoreno village, Jember Regency, is well maintained.